2014
DOI: 10.3892/mmr.2014.2180
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin as a novel biomarker for differentiating between inflammatory bowel disease and irritable bowel syndrome

Abstract: Abstract. The present study aimed to investigate faecal calprotectin as a diagnostic marker to differentiate between patients with inflammatory bowel disease (IBD) and those with irritable bowel syndrome (IBS). A total of 20 healthy control subjects, 26 patients with IBS and 58 patients with IBD, including 22 with ulcerative colitis (UC) and 36 with Crohn's disease (CD), were recruited for the present study. Calprotectin was analysed in stool samples, and C-reactive protein (CRP) and the erythrocyte sedimentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 19 publications
1
50
0
1
Order By: Relevance
“…In one study, FCP levels in IBS patients and healthy control subjects were 44.50 and 35 μg/g, respectively. No statistical difference was identified between the IBS patients and the healthy control subjects . Bonnín Tomàs et al .…”
Section: Discussionmentioning
confidence: 92%
“…In one study, FCP levels in IBS patients and healthy control subjects were 44.50 and 35 μg/g, respectively. No statistical difference was identified between the IBS patients and the healthy control subjects . Bonnín Tomàs et al .…”
Section: Discussionmentioning
confidence: 92%
“…There is a low-grade inflammation of the gut that has been already acknowledged and literature data supports the putative role of the low-grade inflammation in IBS [65][66][67][68]. Several articles addressed this issue, some authors investigated tissue samples [23], while others assessed blood or stool samples [69][70][71][72] in order to detect and determine the inflammation status in IBS patients.…”
Section: Low-grade Inflammationmentioning
confidence: 99%
“…There are already numerous studies that assessed erythrocyte sedimentation rate, C-reactive protein (CRP) from blood sample, fecal calprotectin, and/or lactoferin in order to detect their presence in IBS and/or to calculate their predictive values [71][72][73]. Valuable information was provided by a meta-analysis, although that assessed their cut-off values in order to exclude inflammatory bowel diseases [74].…”
Section: Low-grade Inflammationmentioning
confidence: 99%
“…Fecal calprotectin levels are correlated with the degree of intestinal inflammation, and have been found to increase when neutrophils migrate into the bowel lumen due to the inflammatory process 2. Therefore, fecal calprotectin could help discriminate between IBD and IBS,3 monitor treatment response and endoscopic disease activity,45 and predict relapse for IBD 6. Studies have also shown that fecal calprotectin levels are correlated with endoscopic severity scores5 and the extent of inflammation in Asian patients with UC 7.…”
mentioning
confidence: 99%